Impactos dos programas para a segurança do alimento (BPF e APPCC) adotados por empresas produtoras de alimentos para animais - Coelho, Raquel Cristina Pelicer (2014)
The need to ensure the quality and safety of food becomes increasingly a concern of the entire food production chain, from primary production to final consumption. Feed industry is an important link in this chain, because the food given to livestock can influence the quality and safety of animal products. To ensure food safety adoption of Good Manufacturing Practices (GMP), which, for the animal feed industry has become mandatory implementation in Brazil, from 2003 is required, and preventive approach programs like Hazard Analysis and Critical Control Points (HACCP), whose implementation is not mandatory. This dissertation analyzes the internal and external impacts of the implementation of GMP / HACCP factories in the feed industry associated to Sindirações as well as the perceived difficulties during deployment. We conducted a survey research (survey), through a questionnaire sent to companies, yielding 60 response units. The data were analyzed in order to characterize companies, test possible correlations between the study variables and evaluate corporate groupings (clusters) with similar characteristics. Cluster analysis showed three groups, distinguished from each other mainly by the size of the unit and certifications standards for food safety. Although the quality of the product is a general requirement of the sector, the understanding that the adoption of programs to ensure the safety of foods is important for product quality and essential to the quality of food of animal origin food supplied to the final consumer does not seem to be unanimous in researching industry. It was observed that the plants that meet the most demanding markets tend to adopt these programs as well as certification. The main internal impacts, reported after the implementation of GMP / HACCP have been improvements in the occurrence of food security issues and improving the level of training of production employees, with respect to external impacts, the most cited were improved image brand and the improvement in customer satisfaction.